2022
DOI: 10.1029/2022ms003050
|View full text |Cite
|
Sign up to set email alerts
|

A New Aerosol Dry Deposition Model for Air Quality and Climate Modeling

Abstract: Dry deposition of aerosols from the atmosphere is an important but poorly understood and inadequately modeled process in atmospheric systems for climate and air quality. Comparisons of currently used aerosol dry deposition models to a compendia of published field measurement studies in various landscapes show very poor agreement over a wide range of particle sizes. In this study, we develop and test a new aerosol dry deposition model that is a modification of the current model in the Community Multiscale Air Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…(2020) and Pleim et al. (2022), but also impacts changes in aerosol loads between two periods (in our case, 1850–2000). This may be due to the fact that there are 1850–2000 changes in deposition velocities in both old and new DD and they differ between old and new DD (Figure S2 in Supporting Information ), and/or nonlinear responses of mass concentrations to changes in deposition velocities.…”
Section: Influence Of Mechanistic Dry Deposition On 1850–2000 Changes...supporting
confidence: 55%
See 3 more Smart Citations
“…(2020) and Pleim et al. (2022), but also impacts changes in aerosol loads between two periods (in our case, 1850–2000). This may be due to the fact that there are 1850–2000 changes in deposition velocities in both old and new DD and they differ between old and new DD (Figure S2 in Supporting Information ), and/or nonlinear responses of mass concentrations to changes in deposition velocities.…”
Section: Influence Of Mechanistic Dry Deposition On 1850–2000 Changes...supporting
confidence: 55%
“…Figure 1 indeed shows that new DD largely captures the observed relationship between particle deposition velocities and particle size across forests, grassland, land ice/snow, as well as open water, in contrast to old DD. In particular, like Emerson et al (2020) and Pleim et al (2022), our new scheme better captures observed minima in the relationship. The new scheme's skill is more apparent in MATRIX (Figure 1) than OMA (Figure S1 in Supporting Information S1), which does not represent Aitken mode particles.…”
Section: Model Evaluation Of Observed Relationships Between Depositio...mentioning
confidence: 95%
See 2 more Smart Citations
“…Meteorological and non-asphalt emission inputs, including wildland res, are retrieved from the U.S. EPA's Air QUAlity TimE Series (EQUATES) project 25 and all simulations feature a 10 days spin-up beginning in December 2017 to minimize the inuence of initial conditions. Additional modeling options used here include: (1) an updated parameterization of aerosol deposition in the M3DRY model, 26 including bidirectional ammonia exchange, 27 (2) biogenic emissions generated inline using the Biogenic Emission Inventory System (BEIS) v4, 28 (3) runtime emissions processing using the Detailed Emissions Scaling, Isolation, and Diagnostic (DESID) module, 29 (4) and gas-and aerosol-phase chemistry simulated using the Community Regional Atmospheric Chemistry Multiphase Mechanism (CRACMM) version 1.0 chemical mechanism. 16 The impact of asphalt-related emissions on SOA and ozone is quantied by taking the difference between two photochemical modeling simulations.…”
Section: Photochemical Modeling and Evaluationmentioning
confidence: 99%